2011
DOI: 10.1093/jac/dkr235
|View full text |Cite
|
Sign up to set email alerts
|

National survey of Escherichia coli causing extraintestinal infections reveals the spread of drug-resistant clonal groups O25b:H4-B2-ST131, O15:H1-D-ST393 and CGA-D-ST69 with high virulence gene content in Spain

Abstract: The three clonal groups investigated accounted for 30% of the multidrug-resistant isolates, which gives evidence of an important clonal component in the emergence of resistances among extraintestinal pathogenic E. coli. Notably, a single high virulence clonal group (O25b:H4-B2-ST131) causes approximately 1 in every 10 extraintestinal infections in Spain, representing an important public health threat. A new variant of the ST131 clonal group, which is non-ESBL-producing but trimethoprim/sulfamethoxazole resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
91
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 33 publications
10
91
3
1
Order By: Relevance
“…coli O25:H4-ST131 has been described as an important human extraintestinal pathogen responsible for community-and hospital-acquired urinary tract and bloodstream infections [14,15,30,31,32,33]. This strain is found globally and produces extended spectrum β-lactamase.…”
Section: Discussionmentioning
confidence: 99%
“…coli O25:H4-ST131 has been described as an important human extraintestinal pathogen responsible for community-and hospital-acquired urinary tract and bloodstream infections [14,15,30,31,32,33]. This strain is found globally and produces extended spectrum β-lactamase.…”
Section: Discussionmentioning
confidence: 99%
“…In the 2006 study, it was found that CTX-M-15 had joined CTX-M-14, SHV-12, and CTX-M-9 as a prevalent ESBL type. Thus, the predominant ESBL type had changed quickly, primarily due to the introduction and dissemination of a single clonal group characterized by CTX-M-15, serotype O25b: H4, phylogenetic group B2, and sequence type 131 (ST131), i.e., the international O25b:H4-B2-ST131 clonal group (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…The second objective was to assess the association of particular CTX-M enzymes with the clonal background of strains. The third objective was to compare the distribution of the ST131 isolates with that of the non-ST131 isolates with regard to medical wards, clinical samples, and antibiotic susceptibility in order to better understand the epidemiology of this prevalent clone that often produces CTX-M-15 enzymes (1,6,7,11,15,25,26,30). …”
mentioning
confidence: 99%